2020
DOI: 10.1103/physrevlett.124.153202
|View full text |Cite
|
Sign up to set email alerts
|

Gouy’s Phase Anomaly in Electron Waves Produced by Strong-Field Ionization

Abstract: Ionization of atoms by linearly polarized strong laser fields produces cylindrically symmetric photoelectron momentum distributions that exhibit modulations due to the interference of outgoing electron trajectories. For a faithful modeling, it is essential to include previously overlooked phase jumps occurring when trajectories pass through focal points. Such phase jumps are known as Gouy's phase anomaly in optics or as Maslov phases in semiclassical theory. Most importantly, because of Coulomb focusing in thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…In recent work [46] it was demonstrated that additional Maslov phases (the semiclassical equivalent of Gouy phases) must be included to employ a two-dimensional model for a three-dimensional system, the additional phase for each trajectory is dependent on the number of sign changes of the perpendicular momentum p ⊥ (t ). In this case of the CQSFA these phases can be included by shifting the phase of orbits 3 and 4 by −π/2.…”
Section: Revealing Gouy and Parity Phasesmentioning
confidence: 99%
“…In recent work [46] it was demonstrated that additional Maslov phases (the semiclassical equivalent of Gouy phases) must be included to employ a two-dimensional model for a three-dimensional system, the additional phase for each trajectory is dependent on the number of sign changes of the perpendicular momentum p ⊥ (t ). In this case of the CQSFA these phases can be included by shifting the phase of orbits 3 and 4 by −π/2.…”
Section: Revealing Gouy and Parity Phasesmentioning
confidence: 99%
“…For the small scattering angle, the scattering amplitude predicted by the two-trajectory interference models (even with Gouy's phase modification) diverges because prefactor det( ∂ ps ∂ p f ) there tends to infinite [37]. In our UGRT and GRT, the presence of the term of the square root of the phase difference in the prefactor (see Eq.…”
Section: Calculations Of Pmdsmentioning
confidence: 84%
“…The two-trajectory interference is used to explain for the SFPH where the modulation fringe can be expressed in the cosine function of the phase difference between the two trajectories. Recently, the Gouy's phase [35] is introduced to the two-trajectory strong-field interference picture in a 3D model to compensate for the divergence of the preexponential factors of the semiclassical propagator at focal points [37]. As a result, phase difference in the cosine function will be modified by a νπ/2 phase, where ν is the Maslov index [52][53][54][55].…”
Section: Some Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Our NACTS simulations are equivalent to the scheme presented in Ref. [37], but neglect the interference of trajectories. The result of our NACTS simulation is shown in Fig.…”
mentioning
confidence: 99%